The Routledge handbook of Eurolinguistics - Grzega, Joachim (Routledge, Taylor & Francis Group, 2025)
"The Routledge Handbook of Eurolinguistics provides a comprehensive survey of the typical features among European languages in cultural, geographical or political definitions. Bringing together the latest research in the field, the handbook showcases European traditions of linguistic research on European languages"--
Keywords: Europe -- Languages